Muhammad Natsir: Sumbangannya Terhadap Perjuangan Agama dan Bangsa di Indonesia: Muhammad Natsir: His Contribution Towards Religious and People’s Struggle in Indonesia - Mohamad Noor, Mohamad Muzammil (Journal of Al-Tamaddun, 2022)
This article discusses scholars’ views on Muhammad Natsir’s thoughts. He was one of the prominent political figures and thinkers since the colonial period in Indonesia. As an Indonesia nationalist and political-religious activist, he did not cooperate with the Dutch in pursuit of Indonesia’s independence. Research papers on Natsir’s thoughts and struggles are often penned by local scholars and political-religious writers from that country, including Malaysian authors. This research utilized qualitative approach by conducting analysis through the libraries in Indonesia and Malaysia. Most of the article reviews was conducted through academic study of and general reading on Natsir, especially by Mestika Zed, Deliar Noer and Nurcholis Madjid. Besides that, writing on Natsir’s thoughts and activism was also written by Malaysian scholars such as Anwar Ibrahim, Siddiq Fadhil, Fadhlullah Jamil and Sidek Baba. Hence, the findings of this article attempts to identify the views of these scholars on Natsir’s thoughts and struggles in the political-religious and Indonesian nationalism against the colonial power. This paper also discusses scholars’ views on the contradiction of his political thoughts with Sukarno.